Inovasi sosial untuk perubahan positif terhadap generasi Z sebagai agent of change - Alwi, Muhammad; Fadli, Ahmad Muallam; Kurniawan, Lalu Jawil (Maliki Interdisciplinary Journal, 2024)
This journal examines social innovation for positive change by generation z in response to the ongoing social challenges of the digital era. This research is a means to explore several projects that aim to create positive change, and make Pancasila an inspiration for generation z to innovate, improve the quality of life, and realize a more advanced society.